Unraveling the complex interplay between anti-tumor immune response and autoimmunity mediated by B cells and autoantibodies in the era of anti-checkpoint monoclonal antibody therapies - Soussan, Sarah; Pupier, Guilhem; Cremer, Isabelle; Joubert, Pierre-Emmanuel; Sautès-Fridman, Catherine; Fridman, Wolf Herman; Sibéril, Sophie (Frontiers in Immunology, 2024)
The intricate relationship between anti-tumor immunity and autoimmunity is a complex yet crucial aspect of cancer biology. Tumor microenvironment often exhibits autoimmune features, a phenomenon that involves the interplay of natural autoimmunity and the induction of humoral responses against self-antigens during tumorigenesis. This induction is facilitated by the orchestration of anti-tumor immunity, particularly within organized structures like tertiary lymphoid structures (TLS). Paradoxically, a significant number of cancer patients do not manifest autoimmune features during the course of their illness, with rare instances of paraneoplastic syndromes. This discrepancy can be attributed to various immune-mediated locks, including regulatory or suppressive immune cells, anergic autoreactive lymphocytes, or induction of effector cells exhaustion due to chronic stimulation. Overcoming these locks holds the risk to induce autoimmune mechanisms during cancer progression, a phenomenon notably observed with anti-immune checkpoint therapies, in contrast to more conventional treatments like chemotherapy or radiotherapy. Therefore, the challenge arises in managing immune-related adverse events (irAEs) induced by immune checkpoint inhibitors treatment, as decoupling them from the anti-tumor activity poses a significant clinical dilemma. This review summarizes recent advances in understanding the link between B-cell driven anti-tumor responses and autoimmune reactions in cancer patients, and discusses the clinical implications of this relationship.